A ANALISA KINERJA LOW PRESSURE HEATER (LPH) BERBASIS STANDAR ASME PTC DI PLTU UP GRESIK - Moch Afifur Rosikh; Alviani Hesthi Permata Ningtyas; Ajeng Tri Rahayu (ENIGMA: Engineering in Green Machinery, 2025)
Steam Power Plants (PLTU) have an important role in providing reliable electrical energy for the community and industrial sector. One of the components that affect the thermal efficiency of the generating system is the Low Pressure Heater (LPH), which functions to heat feed water using heat from turbine extraction steam. This study was conducted at LPH 4 Unit 4 at PT PLN Nusantara Power UP Gresik with the aim of assessing the performance of the equipment based on the ASME PTC 12.1 standard, through the analysis of three main parameters, namely Terminal Temperature Difference (TTD), Drain Cooler Approach (DCA), and Temperature Rise (TR). The method used is quantitativedescriptive with operational data collection from July to August 2025. The results of the analysis show that the actual TTD value is much higher than the commissioning value, which indicates a decrease in the effectiveness of heat transfer. Meanwhile, the DCA and TR values are still close to the commissioning value so that the condensate heating and cooling process can be said to be running efficiently. The decline in performance in TTD is thought to be influenced by the age of the LPH, variations in operating loads, and suboptimal data collection patterns. These findings provide important input for PLTU managers in improving system reliability and efficiency through regular maintenance and optimizing performance monitoring methods.